Expression of REX-1, a gene containing zinc finger motifs, is rapidly reduced by retinoic acid in F9 teratocarcinoma cells. - Hosler, B A (1989)
In the presence of retinoic acid (RA), cultured F9 murine teratocarcinoma stem cells differentiate into nontumorigenic cells resembling the extraembryonic endoderm of the early mouse embryo. By differential hybridization screening of an F9 cell cDNA library, we isolated a 1,745-nucleotide cDNA for a gene, REX-1 (for reduced expression), whose steady-state mRNA level began to decline in F9 cells in monolayer culture within 12 h after the addition of RA. By 48 to 96 h after RA treatment of F9 cells in monolayer culture, the REX-1 steady-state mRNA level was more than sevenfold lower than the level in undifferentiated F9 stem cells. The REX-1 mRNA decrease did not result from the reduction in cell growth rate associated with the differentiation process, since the REX-1 mRNA level did not decline in F9 cells that were partially growth arrested after 48 h of isoleucine deprivation. The RA-associated REX-1 mRNA decrease resulted primarily from a reduction in the transcription rate of the REX-1 gene in the presence of RA. In contrast to results in F9 cells, we have been unable thus far to detect REX-1 mRNA in day 7.5 to 12.5 mouse embryo RNA samples or in the P19 teratocarcinoma stem cell line. The putative REX-1 protein identified by DNA sequence analysis contains four repeats of the zinc finger nucleic acid-binding motif and a potential acidic activator domain, suggesting that REX-1 encodes a regulatory protein. The REX-1 gene is not identical to the previously reported murine genes that encode zinc finger-containing proteins.